(3ebGdI aj GdQDjGs - (3CHh Sdje Hf WGgQ GdSLRj GdSLSJGfjs
(3ChdgG (B:s
(3bGd GdQDjG MQcI QHeG GdJi HbjJ ai GdeMSheSGJ jYfi Gf GdbhI GdeJNjdI GPG GfaQOJ HfaSgG aGQZI ai MGd Gdfhe s
(3BNQgG (B:s
(3hbGd gd YOh dfaSg acja jchf UOjbkG dZjQg bGd GdaVd Hf Sgd df JSYhG GdfGS HCehGdce aSYhge HCNdGbce UOb Gddg NjQ GdcdGe Je s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdQGHYIs
(3GfXQg eY GdeNWhW Qbe (B301 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3hgj ebGdI ef cdGe GdajdSha GQSWhWGdjS ai GdQDjGs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(4/253) s
Keywords: (3GdadSaI hGdefWbs